Local Culture Learning in Early Childhood Education Programs: An Analysis of Teacher Strategies in Introducing Lebak Culture, Banten, Indonesia - Rohita; Firmiana, Masni Erika; Suryaningsih, Iin (Journal of Pedagogy and Education Science, 2025)
This study aims to analyze the strategies used by Early Childhood Education Programs (ECEP) teachers in introducing Lebak’s local culture to preschool children within early childhood education programs. A descriptive survey method with a cross-sectional design was used to capture teachers' strategies at a specific point in time. This study involved 40 respondents from 28 ECEP institutions, including public and private schools, selected through purposive sampling. Data were collected using a structured questionnaire consisting of demographic questions and open-ended questions exploring cultural content, teaching methods, and media. The collected data were analyzed using simple statistical methods, including graphical representation and narrative description. The results showed that the most common cultural content introduced was Baduy culture, followed by traditional food and clothing. Storytelling emerged as the most frequently used method, followed by questions, video presentations, demonstrations of real objects, and observation of images. Storytelling is preferred because it allows children to understand cultural narratives in an interesting and meaningful way. However, the storytelling techniques used by teachers often focus more on conveying information than stimulating higher-order thinking skills. In addition, video media is widely used because of its effectiveness in attracting children's attention and simplifying cultural concepts, but teachers need further training to improve the quality of educational videos. In conclusion, ECEP teachers in Lebak, Banten, have implemented various strategies to introduce local culture. However, improvements are needed, especially in improving questioning techniques in storytelling and optimizing educational video production.